Peran dan Fungsi Litbang dalam Mendukung Sistem Inovasi Daerah Provinsi Jambi (Role And Function Of Research And Depelovment Board To Provide SIDa In Jambi Provincial) - Sayid Syekh (Universitas Batanghari Jambi, 2019)
The purpose of development is to create a prosperous society. This goal is inseparable from the role of Research and Depelovment Board in the development process. This research raises the issue of the role of the Balitbangda and the strengthening of the Regional Innovation System (SIDa) of Jambi Province. Data is collected by interview, observation and documentation. Then the data is analyzed using the triungulation method. The result is the Balitbangda is the secretariat for strengthening the Regional Innovation System of Jambi Province. The steps taken in the formation of the Coordination Team are by establishing the Jambi Province Regional Innovation System Socialization Team and conducting socialization. collaboration with the research institutions and Universities. Cooperating with industry. Strengthening the Regional Innovation System is realized will not run smoothly without close coordination between related parties, both those under the coordination of the government and private institutions and universities / research institutions. The Balitbangda's support in strengthening the Regional Innovation System (SIDa) of Jambi Province is by implementing Kelitbangan based on the needs of the industry and the community.